Features of training specialists using innovative approaches - Knysh, Inna; Tiahur, Liubomyra; Ivanova, Victoria; Vasiutynska, Yelena; Shovsh, Kateryna (My University, 2023)
The article examines the peculiarities of training specialists through the use of innovative approaches. The article shows the methodological concept of purposeful formation of competitive specialists in the process of professional training, which represents the main innovative approaches to the study of the problem of training specialists. The purpose of the research is revealed, in which the peculiarities of the training of specialists using innovative approaches are revealed. Two types of these approaches to high-quality training of specialists are identified. The innovative approach in education is considered through the use of the proposed model and through the ability to design and model the programmed educational process in a higher education institution with the mandatory application of various innovative approaches. The authors highlight the main components of educational innovation in the article. Prospective directions of educational innovation are highlighted. The necessity of applying innovative approaches in the system of education of future specialists is proven and the need for active assimilation of educational information is shown, the development of key competencies, professional growth and ensuring the competitiveness of future specialists on the labor market in the modern world are proven. The main innovative technologies in education, which have recently been introduced into the practice of higher education, are considered.

У статті розглянуто особливості підготовки фахівців шляхом застосування інноваційних підходів. У статті показано методологічну концепцію цілеспрямованого формування конкурентоспроможних спеціалістів у процесі професійної підготовки, яка репрезентує основні інноваційні підходи до дослідження проблеми підготовки фахівців. Розкрито мету дослідження в якій виявлено особливості підготовки фахівців з використанням інноваційних підходів. Означено два види цих підходів до якісної підготовки фахівців. Інноваційний підхід в освіті розглянуто через використання запропонованої моделі та через здатність проектувати і моделювати запрограмований освітній процес у закладі вищої освіти з обов’язковим застосуванням різних інноваційних підходів. Автори виділяють у статті основні складові освітньої інновації. Висвітлено перспективні напрями освітньої інновації. Доведена необхідність застосування інноваційних підходів в системі освіти майбутніх фахівців та показано необхідність активного засвоєння навчальної інформації, доведено розвиток ключових компетентностей, професійне зростання й забезпечення конкурентоспроможності майбутніх фахівців на ринку праці у сучасному світі. Розглянуто основні інноваційні технології в освіті, які останнім часом впроваджуються в практику вищої освіти.
Особливості підготовки фахівців за допомогою інноваційних підходів
Keywords: innovations; training of specialists; innovative approaches; pedagogical technologies; pedagogical process of a higher school; інновації; підготовка фахівців; інноваційні підходи; педагогічні технології; педагогічний процес вищої школи